Enhancing Instruction In Electronics: A Whole-Brain Approach Utilizing Differentiated Activities - Goyal, John Kenneth C.; Custodio, Eunice B. (Future Science / FSH-PH Publications, 2025)
Enhancing teaching strategies in teaching electronics contributes to Sustainable Development Goal 4 (Quality Education) by promoting inclusive and effective learning. Additionally, Priority Area 15 of the EDCOM 2 Year 2 Report highlights the importance of innovative pedagogical approaches to improve engagement and academic per-formance in higher education. This study evaluates the effectiveness of differentiated activities grounded in the whole-brain approach in teaching 80 first-year Electronics Technology students at Valenzuela City Technological College, selected through purposive sampling. Mean, percentage, standard deviation, and t-tests for correlated and independent samples were used for statistical analysis. Findings indicate that prior to implementing differentiated activities, stu-dents exhibited moderate engagement when taught using conven-tional methods. However, engagement significantly increased after the introduction of differentiated activities grounded on the whole brain approach. Pre-test scores for both control and experimental groups did not exceed 50%, indicating low student engagement and academic performance. In contrast, post-test scores improved sig-nificantly, confirming the effectiveness of differentiated activities grounded on the whole brain approach in teaching electronics. De-spite the frequent use of differentiated strategies, instructors at Valenzuela City Technological College often overlook students' pre-ferred learning styles, limiting the full potential of whole-brain in-struction. These findings emphasize the need for instructional ap-proaches tailored to diverse learning needs to maximize student engagement and academic success. In response, this study proposes a training plan for college instructors to enhance the application of differentiated activities grounded on the whole brain in teaching electronics education.